Pengambilan Keputusan Pada Muallaf Perempuan Dewasa Awal - Amatullah, Muna Faiza, Dr. Nisa Rachmah N.A., M.Si, Psi, Drs. M. Darojat Ariyanto, M.Ag (2017)
Islam is a religion of the world's second-largest after Christianity. However, in the last few years the muslim population experienced a significant increase. This increase is not only due to population growth but also the religious conversion. The conversion requires a complex decision-making process. The main objective of this research is to understand the decision-making process on individuals who perform religious conversion or referred to as muallaf. This research focused on the early adulthood of female converts.This research is qualitative research phenomenological approach. The informant is composed of 4 muallaf under criterion 1) women aged 20-40 years; 2) made the creed of no more than 3 years ago; 3) personal decision. Method of data collection is in-depth interviews. While the method of data analysis using the method of fenomenlogi from Moustakes.The results showed that 1) Time praconversion has 3 State a) confusion in religion; b) old religion is strong; c) religions are less powerful; 2) decision-making process using an intuitive approach, because it tends to be fast and not pass through the stages of the election alternative while factors that support decision making i.e. a) subjectif utility; b) beliefs; (c) awareness. 3) conversion Types are grouped into 2 that is sudden and gradual while conversion motives are grouped into 3 namely motif of intellectual, spiritual and afeksional. 4) Internalization of Islamic values are grouped in 3 thing i.e. (a) the manner of delivery; (b) the type of words used; (c) the material presented. 5) Pascaconversion have the negative side in the form of conflict and pressure and the positive side in the form of tranquility and get what was sought and happiness